2022
DOI: 10.1101/2022.08.09.22278279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online anxiety resources for Canadian youth: a systematic environmental scan

Abstract: Introduction: In a recent child health research priority setting exercise conducted in Alberta (CA), youth identified mental health as a priority topic. Specifically, youth were interested in understanding what the early signs and symptoms of anxiety were, and when they should seek help. Objective: The objective of this study was to understand what information is currently available online for Canadian youth about the signs and symptoms of anxiety, what resources are available for self-assessment, and what ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…One response suggested that the Niggle app, [47] produced by the Kid's Helpline, may not be age appropriate as this age demographic would nd identi cation as a "kid" to be off-putting. A different reviewer suggested that this app could, however, be a useful resource for "nippers" (an SLSA junior development program for children aged [5][6][7][8][9][10][11][12][13][14]. Some toolkits (such as Mental Wealth [33] and Niggle [47]) were identi ed as appropriate for younger people within the target age group, but potentially not relevant for those in their older teens and twenties.…”
Section: Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…One response suggested that the Niggle app, [47] produced by the Kid's Helpline, may not be age appropriate as this age demographic would nd identi cation as a "kid" to be off-putting. A different reviewer suggested that this app could, however, be a useful resource for "nippers" (an SLSA junior development program for children aged [5][6][7][8][9][10][11][12][13][14]. Some toolkits (such as Mental Wealth [33] and Niggle [47]) were identi ed as appropriate for younger people within the target age group, but potentially not relevant for those in their older teens and twenties.…”
Section: Contentmentioning
confidence: 99%
“…Few studies have focused on health toolkits in general despite their wide implementation in health promotion. [17] There have been previous environmental scans of online mental health resources for young people, [14,15] but none were found that have focused on toolkits speci cally. Thus, there is a signi cant literature gap that validates the toolkit focus we have taken.…”
Section: Strengths Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation